Influence of maternal occupation on adverse pregnancy outcomes in a Nigerian tertiary health facility - Nwoga, Hope O.; Ajuba, Miriam O.; Igweagu, Chukwuma P. (International Journal Of Community Medicine And Public Health, 2021)
Background: There is accumulating evidence that the type of work and environmental exposures in the work environment during pregnancy may have adverse effects on fetal development and pregnancy outcome. The objective was to determine the influence of maternal occupation on adverse pregnancy outcomes. Methods: The study was a prospective hospital based study conducted at the obstetrics and gynecology department of a tertiary health facility in Nigeria. All the data were retrieved from the ante natal and delivery card of all the women that delivered at the unit within the time of data collection. Data was analyzed using SPSS version 25 and variables were presented as frequencies, percentages, means, and standard deviation. Bivariate analysis was done using chi-square test. The level of significance was set at p value ≤ 0.05. Results: Maternal occupation did not significantly affect the gestational age at delivery (X2=10.143, p=0.428) and birth weight (X2=16.807, p=0.079) however, it significantly affected the still birth (X2=28.134, p=0.002). Agricultural, forestry and fishery workers and plant and machine operators were about 8 times and 17 times more likely to have still birth than the unemployed respectively. Conclusions: There were substantial differences in the risk of adverse pregnancy outcomes between the different occupational groups.